PENGEMBANGAN SISTEM PENDIDIKAN PESANTREN (Studi Kasus di Pondok Pesantren Terpadu Al-Kamal Kunir Wonodadi Blitar) - Al Muiz, Mochamad Nasichin (LP2M IAIN Tulungagung, 2018)
Abstract Islamic boarding schools as an islamic education institutions which has a big role in the efforts to educate the life of nation, should keep up with the times. Al-Kamal Compacted a Religious Boarding School is a pesantren that has a combination of modern and salaf or called to be integrated. This study uses qualitative approach with the subject is Al-Kamal Compacted a Religious Boarding School in Kunir Village, Wonodadi District, Blitar Regency, the object emphasizes the development of pesantren institutions, curriculum and educational methods. The results of this study indicate that Al-Kamal Integrated Islamic Boarding School has been developing pesantren institutions such as founding Madrasah Diniyah Al-Kamal, Majlis Murottil Qur'an, Ma'had Aly Al-Kamal, Al-Kamal Language Institute, Al-Kamal Library, Computer Laboratory. Keywords: Pesantren Educational System, Institutions, Curriculum and Educational Methods